Impact of traumatic experiences on obsessive-compulsive disorder: a study of Palestinians in the Gaza Strip – a conflict area - Nadin Hannoon; Basel El-Khodary; Zhongming Zhang (European Journal of Psychotraumatology)
Objective: Prior research has indicated a possible relationship between obsessive-compulsive disorder (OCD) and trauma that appears to affect symptom severity and comorbidity. The Gaza Strip, a region characterised by ongoing violence and conflict, would benefit from further study to address psychopathology in the context of psycho-traumatology. Considering these circumstances, in this study, we investigated the prevalence of trauma aetiology among OCD patients and its impact on the clinical picture by studying the effects of trauma on three different levels of trauma-aetiology: (1) history of trauma exposure (TE-OCD), (2) individual perception of OCD as trauma-related (TR-OCD), and (3) the onset of OCD within six months post-trauma (PT-OCD).Methods: This cross-sectional study included 103 Gazans diagnosed with OCD, aged 18–56 years. Semi-structured clinical interviews, including self-report measures, were used to collect demographic and diagnostic data.Results: Out of 103 participants, 77.7% reported a history of trauma (TE-OCD), 29.1% perceived their trauma as a cause of OCD (TR-OCD), and 18.4% developed their symptoms within six months of the trauma (PT-OCD). No significant correlation was found between the severity of OCD symptoms and a history of trauma exposure. Statistical differences in symptom severity were found across TR- and PT-OCD levels of trauma-aetiology. However, after controlling for major depressive disorder (MDD), these differences were observed only for obsessions.Conclusions: These findings reveal that trauma is common among OCD patients in Gaza and could be a major predisposing factor. The perception of trauma as a cause and the time between trauma exposure and OCD onset could impact the clinical picture of OCD in terms of symptom severity and increased MDD comorbidity.